Erythroferron: Modern Concepts of Its Role in Iron Metabolism Regulation - VT Sakhin; NV Kremneva; AV Gordienko; OA Rukavitsyn (Клиническая онкогематология)
The article presents the results of experimental and clinical studies evaluating the importance of supposed erythroid regulators of hepcidin levels and mechanism of their action. It demonstrates that the role of growth differentiation factor 15 and twisted gastrulation protein homolog 1 in regulation of hepcidin levels in humans has not been confirmed yet. The data confirming the importance of erythroferron in the pathogenesis of anemia related to blood loss, hemolysis, and hereditary anemias with ineffective erythropoiesis are presented. The studies demonstrated that erythroferron plays the greatest role in the regulation of hepcidin levels in pathological conditions and at stress and does not play a leading role in erythropoiesis under normal conditions. Erythroferron suppresses the hepcidin synthesis by affecting the liver cells directly through an unknown receptor cellular pathway